The Role of Instagram Content @inspira.sien in Encouraging Online Self-Disclosure among Chronic Disease Warriors - Deanda Dewindaru; Fitria Hani Aprina; Husnaeni Fauziah Amani (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2025)
This study aims to analyze how the Instagram account @inspira.sien plays a role in encouraging online self-disclosure among chronic disease fighters through the presentation of educational, informational, entertainment, and collaborative content. Using a qualitative approach with content analysis and in-depth interviews with five active followers, this study found that entertainment content was the most dominant type of content and had the highest engagement rate of 365.66%, followed by informational, educational, and collaborative content. The results show that light-hearted content that is relevant to the audience's personal experiences is more effective in encouraging emotional engagement and self-disclosure in the comments section. Factors that contribute to self-disclosure include comfort, personality, trust, intimacy, reciprocity, anonymity, gender, and culture. Positive responses from the community and admin @inspira.sien reinforce a sense of acceptance, safety, and motivation to share. This study confirms that social media can be a safe and supportive space for people with chronic illnesses to express themselves, reduce social stigma, and improve mental well-being through online emotional support.